Muscarinic acetylcholine receptor X-ray structures: potential implications for drug development - Kruse, Andrew C. (2014)
Muscarinic acetylcholine receptor antagonists are widely used as bronchodilating drugs in pulmonary medicine. The therapeutic efficacy of these agents depends on the blockade of M(3) muscarinic receptors expressed on airway smooth muscle cells. All muscarinic antagonists currently used as bronchodilating agents show high affinity for all five muscarinic receptor subtypes, thus increasing the likelihood of unwanted side effects. Recent X-ray crystallographic studies have provided detailed structural information about the nature of the orthosteric muscarinic binding site (the conventional acetylcholine binding site) and an 'outer' receptor cavity that can bind allosteric (non-orthosteric) drugs. These new findings should guide the development of selective M(3) receptor blockers that have little or no effect on other muscarinic receptor subtypes.